Management of Children's Aggressiveness when Playing Competitive Games in the English Class - Castellanos Andrea (Universidad Nacional de Colombia, 2002)
Human behaviour has been a changing aspect during the history of mankind. Humanity has learned to get along with others; but the behavioural stage has been very difficult to control across the time, because everyone has his/her own interests. In this article, I will describe some factors that affect children's aggressive behaviour when playing competitive games and some strategies that may be considered when guiding those types of games with young learners in the English class. These can lead, as I found in my study, to deeper understandings of children's conducts as well as to improvement in classroom management.